INFLUENCE OF SPIRAL PATTERNS ON DYNAMICAL EVOLUTION OF GALACTIC DISC - Paliienko, M. V. (Одеські астрономічні публікації, 2007)
This paper reports on the theoretical investigation of evolution of the Galactic disc, taking in account the influence of spiral patterns. The spiral patterns can be considered as some kind of indicators of the dynamical processes in the disc. We investigate influence of spiral patterns on the surface density of gas, stars and metallicity in time at the solar neighbourhood. We consider the models in the approximation of instantaneous recycling of material. Results of models are compared with observational data, that give possibility to predict correct model for evolution of the Galactic disc. The results of the model predictions differ significantly comparing to the case of the standard Galactic evolutionary model.